Fatores associados à fragilidade em idosos hospitalizados: uma análise clínica e social - Gonçalves, Tânia Cassiano Garcia (2024)
OBJECTIVES: To analyze frailty and its associated factors in hospitalized elderly people METHODS: Exploratory, observational, cross-sectional study, descriptive design, quantitative analytical approach with correlation between variables, aiming to quantify the strength and relationship between them. The following research instruments were applied: Participant Characterization Instrument; Subjective Assessment of Frailty; Tilburg Frailty Indicator; Scale of Independence in Activities of Daily Living – Katz; Lawton Instrumental Activities of Daily Living Scale. In the comparative analyses, the Mann-Whitney test was used to verify the difference in the scale scores between the two groups. The Kruskal-Walli’s test was used to verify the difference in the scale scores between three or more groups. RESULTS: The sample comprised 125 participants. The median age was 70, with 72 years being the median age. There was a predominance of males (53.6%). The average amount of medication used by the participants was between four and five medications. In the subjective assessment of frailty, it was noted that 75 patients (60%) were considered frail; 38 patients (30.4%) pre-frail; and 12 patients (9.6%) non-frail. On the Tilburg scale, 59 patients were considered non-frail (47.2%) and 66 were considered frail (58.2%). In the analysis of the Katz scale, only 5 patients (4%) were dependent. There was a significant correlation between frailty and functionality in the bivariate analyses, both by the Subjective Frailty Assessment scale and by the Tilburg scale. The correlation between Subjective Frailty Assessment and Katz was positive and moderate. On the other hand, the correlation between Subjective Frailty Assessment and Lawton was inverse (also moderate). There was a significant difference. Concerning the variable Diabetes Mellitus and falls; similar to the variable "Describes Health" (p <0.001). A post hoc analysis was performed in search of comparisons in pairs due to the significant difference for the variable "Describes Health". In comparison with demographic and/or clinical data, there was a difference in the Tilburg scores according to education and personal income; and the variable "Describes Health" also showed a significant difference. In the comparison of the data with the Katz scores, there was no significant difference. In the Lawton scores, differences were observed according to the variables "With whom they live", "Education" and "Describes Health". Lawton's post hoc analysis showed a difference in the "living alone" or "living with others" groups. Lawton's post hoc analysis showed a difference between “living alone” and “living with others”. As for the “Describes Health” variable, the difference between the groups was regular and good/very good/excellent. CONCLUSION: Physical frailty and its associated factors in hospitalized elderly people are prevalent and multifactorial. The study's conclusion reinforces the need for a comprehensive approach by health teams to deal with frailty, preventing its progression, or even reversing it. Identifying frailty and understanding its associated factors are fundamental for implementing health care aimed at this population; to prevent, reverse, or avoid the progression of this syndrome. Actions that can have a significant impact on the planning of health actions that will improve the quality of life of hospitalized elderly people, making the study relevant to both clinical practice and the development of health policies addressed for this population.